2017
DOI: 10.1038/s41598-017-01907-w
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal insulin enhances brain functional connectivity mediating the relationship between adiposity and subjective feeling of hunger

Abstract: Brain insulin sensitivity is an important link between metabolism and cognitive dysfunction. Intranasal insulin is a promising tool to investigate central insulin action in humans. We evaluated the acute effects of 160 U intranasal insulin on resting-state brain functional connectivity in healthy young adults. Twenty-five lean and twenty-two overweight and obese participants underwent functional magnetic resonance imaging, on two separate days, before and after intranasal insulin or placebo application. Insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 71 publications
3
42
0
2
Order By: Relevance
“…This corresponds to data from anorexia cohorts which report that individuals with anorexia have a reduced appreciation of sweet tastes (81). In contrast, insulin is postulated to have an anorexigenic effect in the brain (82,83), partly through its inhibition of the orexigenic agouti-related peptide (AgRP) and neuropeptide Y (NPY) neurons (84,85). This may contradict the putative risk-decreasing effect of insulin on anorexia we observed in our study, however, there is evidence of a significant sexual dimorphism in this phenomenon.…”
Section: Discussionsupporting
confidence: 83%
“…This corresponds to data from anorexia cohorts which report that individuals with anorexia have a reduced appreciation of sweet tastes (81). In contrast, insulin is postulated to have an anorexigenic effect in the brain (82,83), partly through its inhibition of the orexigenic agouti-related peptide (AgRP) and neuropeptide Y (NPY) neurons (84,85). This may contradict the putative risk-decreasing effect of insulin on anorexia we observed in our study, however, there is evidence of a significant sexual dimorphism in this phenomenon.…”
Section: Discussionsupporting
confidence: 83%
“…In this sense, a plausible interpretation could be that, at higher levels of visceral adiposity, there may be a need to increase the connectivity strength within mIns-frontoparietal network to drive homeostatic behavior in the face of reduced homeostatic information -linked to the reduced connectivity within the mIns-HYP/BNST network. Interestingly, in a recent report it has been shown that functional connectivity between homeostatic and cognitive centers of the brain could be modulated by insulin sensitivity (39). Future research may attempt to investigate how hormonal factors interact with the relationship between visceral adiposity and brain connectivity measurements.…”
Section: Discussionmentioning
confidence: 98%
“…Recent imaging studies characterized a limited number of cortical and sub-cortical brain regions that respond to the peptide hormone, including the hypothalamus 6 . Insulin also impacts the functional inter-connection of these areas 7 , which underlines its importance in the control of larger networks within the brain.…”
mentioning
confidence: 99%